The genetic landscape of metaplastic breast cancers and uterine carcinosarcomas. Issue 4 (19th February 2021) - Moukarzel, Lea A.; Ferrando, Lorenzo; Da Cruz Paula, Arnaud; Brown, David N.; Geyer, Felipe C.; Pareja, Fresia; Piscuoglio, Salvatore; Papanastasiou, Anastasios D.; Fusco, Nicola; Marchiò, Caterina; Abu‐Rustum, Nadeem R.; Murali, Rajmohan; et al.
Abstract : Metaplastic breast carcinoma (MBC) and uterine carcinosarcoma (UCS) are rare aggressive cancers, characterized by an admixture of adenocarcinoma and areas displaying mesenchymal/sarcomatoid differentiation. We sought to define whether MBCs and UCSs harbor similar patterns of genetic alterations, and whether the different histologic components of MBCs and UCSs are clonally related. Whole‐exome sequencing (WES) data from MBCs ( n  = 35) and UCSs ( n  = 57, The Cancer Genome Atlas) were reanalyzed to define somatic genetic alterations, altered signaling pathways, mutational signatures, and genomic features of homologous recombination DNA repair deficiency (HRD). In addition, the carcinomatous and sarcomatous components of an additional cohort of MBCs ( n  = 11) and UCSs ( n  = 6) were microdissected separately and subjected to WES, and their clonal relatedness was assessed. MBCs and UCSs harbored recurrent genetic alterations affecting TP53, PIK3CA, and PTEN, similar patterns of gene copy number alterations, and an enrichment in alterations affecting the epithelial‐to‐mesenchymal transition (EMT)‐related Wnt and Notch signaling pathways. Differences were observed, however, including a significantly higher prevalence of FAT3 and FAT1 somatic mutations in MBCs compared to UCSs, and conversely, UCSs significantly more frequently harbored somatic mutations affecting FBXW7 and PPP2R1A as well as HER2 amplification than MBCs. Genomic features of HRD and biallelic alterations affecting bona fide HRD‐related genes were found to be more prevalent in MBCs than in UCSs. The distinct histologic components of MBCs and UCSs were clonally related in all cases, with the sarcoma component likely stemming from a minor subclone of the carcinoma component in the samples with interpretable chronology of clonal evolution. Despite the similar histologic features and pathways affected by genetic alterations, UCSs differ from MBCs on the basis of FBXW7 and PPP2R1A mutations, HER2 amplification, and lack of HRD, supporting the notion that these entities are more than mere phenocopies of the same tumor type in different anatomical sites. Abstract : Metaplastic breast carcinoma (MBC) and uterine carcinosarcoma (UCS) are rare aggressive cancers, characterized by an admixture of adenocarcinoma and areas displaying mesenchymal/sarcomatoid differentiation. In this study, we investigate whether MBCs and UCSs harbor similar patterns of genetic alterations and mutational signatures using whole‐exome sequencing data. In addition, we examine whether the different histologic components of MBCs and UCSs are clonally related.